The G20 as a Multilateral Force - Rakhra, Kanica (CEBRI-Revista: Brazilian Journal of International Affairs, 2024)
This paper highlights how the G20 as a grouping works against odds to bring forth voices from the Global South while balancing the requirements of the Global North. It also highlights the focus of the grouping on the Sustainable Development Goals and what it means to be halfway towards Agenda 2030. Most importantly, the paper explains how the G20 is slowly becoming a force to reckon with within the multilateral world.